First clinical applications for the NIR-II imaging with ICG in microsurgery - Wu, Yifan; Suo, Yongkuan; Wang, Zheng; Yu, Yifeng; Duan, Shuang; Liu, Hongguang; Qi, Baiwen; Jian, Chao; Hu, Xiang; Zhang, Dong; Yu, Aixi; Cheng, Zhen (Frontiers in Bioengineering and Biotechnology, 2022)
In microsurgery, it is always difficult to accurately identify the blood supply with ease, such as vascular anastomosis, digit replantation, skin avulsion reconstruction and flap transplantation. Near-infrared I (NIR-I) imaging has many clinical applications, while near-infrared II (NIR-II) imaging has also been reported to be used in a few clinical fields recently, its penetration distance and noninvasive characteristics coincide with the needs of microsurgery. Therefore, we choose to use portable near-infrared II imaging instrument and the Food and Drug Administration (FDA) approved indocyanine green (ICG) to improve the operation efficiency in 39 patients. The anastomotic vessels and the salvaged distal limbs can be visualized after intravenous injected ICG. This technique enables identification of perforator vessels and estimation of perforator areas prior to the flap obtention and made it easier to monitor the prognosis. The use of portable NIR- II imaging with ICG as an operative evaluation tool can enhance the safety and accuracy of microsurgery.